Virtual Reality-Based Learning Environments in Teacher Training: New opportunities and challenges - Stavroulia, Kalliopi Evangelia; Baka, Evangelia; Lanitis, Andreas; Magnenat-Thalmann, Nadia (My University, 2017)
Nowadays, teachers face unprecedented challenges due to the diversity of the student population that is characterized by different cultural and language backgrounds, different levels of knowledge, different learning needs and increased levels of antisocial behavior. Classrooms have become more complex and dynamic environments and thus teachers need to constantly adapt their practices to the needs of individual learners and groups. Nevertheless, research reveals that teachers are not trained for the demanding and constantly changing requirements of the profession. Additionally, the lack of university-school connection deprives beginning teachers from learning through mentoring from experienced colleagues. To address the above challenges, our work aims to contribute to the strengthening of the profile of the teaching profession through the enhancement of teachers’ professional development, using a contemporary virtual reality-based framework. Virtual Reality (VR) offers engaging and immersive experiences, allowing teachers to experience real world classroom situations which require rapid thinking and quick analysis for effective management. The long term goal is to offer, a contemporary, safe and low-cost in-service and pre-service teacher VR-based training instrument that allows users to learn from their mistakes without consequence for the students. The project approach is both innovative and complementary towards other projects already carried out as well as focused on teacher training. The logical framework approach used to support the development of the proposed tool is divided into five main phases. The first phase concerns the definition of the pedagogical framework that will form the basis for the design of effective training scenarios that will be developed within the virtual environment. Questionnaire-based surveys, focus groups and interviews were used in an effort to identify the real training needs of in-service teachers. The second phase deals with the development of the competence framework for using VR in teacher training. Defining a competence model is essential before the development of the VR application as it is essential to assess teachers’ competences. The third phase concerns the design of the training scenarios for the VR application, while the fourth phase concerns the development of VR application based on the scenarios. The final phase has to do with assessing the impact of the VR application. Preliminary results obtained through the evaluation of teachers needs and through the evaluation of prototype VR teacher training applications indicate that there is a lack of practice in teacher training and teachers need further training in teaching students with special learning needs, in confronting students with disorders such as vision, hearing and speech disorders, in behavior management and in body language. Additionally, the results reveal that teachers need training regarding student’s behavioral disorders (including violence, aggression), health disorders, learning disabilities and Attention Deficit Hyperactivity Disorder (ADHD). Furthermore, the most significant of the results lies in teachers’ need of additional training for all the above-mentioned issues not in theory, but in practice within a virtual classroom environment.
Keywords: Virtual reality; Teacher training